Hubungan antara faktor keturunan, pembawaan, dan lingkungan pendidikan dalam membentuk potensi anak didik - Nada, Rifa Qotrun; Hanif, Ma'mun (Jurnal Pendidikan Agama Islam, 2025)
This research seeks to explore how genetic factors, inherent characteristics, and the learning environment interact to shape children's potential.The research employs a literature review method by analyzing relevant previous studies. Heredity provides the biological and genetic foundation that influences intelligence, talents, and personality. Meanwhile, innate traits function as initial potentials possessed since birth, which require stimulation to develop optimally. The educational environment, both formal and non-formal, serves as a crucial medium that facilitates this development through teaching, habituation, and social interaction. The findings indicate that a child’s potential is not solely determined by genetic factors, but rather results from the dynamic interaction between heredity, innate traits, and educational environment. Therefore, efforts to develop children’s potential must consider a balance between empowering internal factors and providing a supportive educational setting. This study is expected to offer theoretical contributions to educational psychology and serve as a practical reference for designing holistic learning strategies.